Effect of alkali on the structure of cell envelopes of Chlamydia psittaci elementary bodies. - Narita, T (1976)
Suspensions of isolated cell envelopes of infectious elementary bodies (EB) of Chlamydia psittaci at alkaline pH showed a rapid, extensive decrease in absorbance, accompanied by the release of a cell envelope component in a sedimentable form. This phenomenon was observed both at 0 C and with envelopes which had been previously heated to 100 C. Monovalent and divalent cations effectively inhibited the turbidity loss, whereas ethylenediaminetetraacetate (EDTA) caused an accelerated decrease in turbidity. The turbidity loss observed after incubation of the envelopes at alkaline pH could be reversed to the level of the initial value by dialysis against distilled water containing Mg2+. Thin-section electron photomicrographs of purified EB exposed to alkaline buffer with EDTA revealed the loss of the internal contents of cells, but these cells still maintained their round shapes. The cell surface of treated EB appeared pitted in negatively stained preparations, whereas intact EB had a smooth surface. Electron microscopic studies on negatively stained preparations of the clear supernatant obtained after the treatment of the envelope with alkaline buffer containing EDTA demonstrated the presence of spherical particles, approximately 6 to 7 nm in diameter, and rodlike particles, which appeared to be made up of two or more spherical particles.